Cortisol increases the return of fear by strengthening amygdala signaling in men. (May 2018) - Kinner, Valerie L.; Wolf, Oliver T.; Merz, Christian J.
Highlights: Cortisol promotes the reinstatement of fear. This effect is characterized by increased fear-related amygdala activation. A cortisol-induced return of fear can be observed in men but not in women. Cortisol effects on the neural correlates of fear recovery are sex-dependent. A neuroendocrine mechanism, explaining how stress may promote fear relapse. Abstract: Relapses represent a major limitation to the long-term remission of pathological fear and anxiety. Stress modulates the acquisition and expression of fear memories and appears to promote fear recovery in patients with anxiety disorders. However, the neural correlates underlying stress hormone effects on the return of fear in humans remain unexplored. Likewise, little is known about the interactions between sex and stress hormones on return of fear phenomena. In this functional magnetic resonance imaging study, 32 men and 32 women were exposed to a fear renewal paradigm with fear acquisition in context A and extinction in context B. On the following day, participants received either cortisol or placebo 40 min before return of fear was tested in both contexts in a renewal and reinstatement test. Cortisol increased differential conditioned skin conductance responses in the extinction context B following reinstatement in men but not in women. On the neural level, this effect was characterized by enhanced fear-related activation in the right amygdala in men, while an activation decrement in this region was observed after cortisol treatment in women. Our results revealed that cortisol promotes the return of fear in men by strengthening a key node of the fear network – the amygdala. We thereby provide novel insights into a sex-specific mechanism mediating stress-induced fear recovery which may translate into different relapse risks and treatment strategies for men and women.